ANALYSIS OF TRANSLATION ERRORS IN GOOGLE TRANSLATE ARABIC TEXTS INTO INDONESIAN IN THE BOOK IHYA' ULUMUDDIN - M. Alaika Nasrullah; Anyes Lathifatul Insaniyah; Mauliddah Khasanah (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2025)
This research aims to identify the errors of Google Translate in translating Arabic  text into Indonesian in the book Ihya' Ulumudin, specifically in the fields of syntax  and semantics. The type of research used in this study is library research, which is  a data collection technique involving a review of books related to the problem to be  solved. The data used in this study is from the book "Ihya' 'Ulumuddin" volume 3,  chapter "Al-Riya'u Al-Khafi" which is more hidden than the crawling of ants. Data  analysis in this study was done by collecting data, recording errors, describing  errors, and evaluating errors. The results of this study are that Google Translate  still has many shortcomings in translating Arabic text into Indonesian, especially  for yellow book texts which are heavily laden with nahwu and shorof rules. As for  the errors in Google Translate in the field of syntax found in this study, they are:  errors in translating superlative verbs, errors in translating plural sentences,  errors in translation, errors in translating compound structures, and errors in  Google Translate's translation of passive participles. Google's semantic errors  include: mistranslation of the same letters with different vowel marks, incorrect  word choice, inaccurate translation of hidden pronouns, Google's error in  translating the letter qod, grammatical errors, and errors in translating the benefits  of letters. The implications of this research indicate that the use of Google Translate  as a tool for translating Arabic religious texts, particularly classical texts, needs to  be accompanied by adequate linguistic understanding. These findings can also  serve as a reference for teachers, students, and Arabic translators to be more  critical in using translation machines and to encourage the development of  translation technology that is more sensitive to the syntactic structure and semantic  meaning of classical Arabic.